Experimental and analytical studies of a novel aluminum foam filled energy absorption connector under quasi-static compression loading. (15th January 2017) - Wang, Yonghui; Liew, J.Y. Richard; Lee, Siew Chin; Wang, Wei
Highlights: A novel aluminum foam filled energy absorption connector was proposed. Aluminum foam and pleated plate were used for energy absorption. Experimental study on the energy absorption performance of the connector. Analytical model was proposed to predict the load-displacement curve. Abstract: A novel energy absorption connector with pleated plate and aluminum foam as energy absorber was proposed to be inserted between the blast resistant façade and building to absorb blast energy and reduce blast load transferred to the building. The energy absorption performance of the connector under quasi-static compression loading was first studied by using experimental method. The deformation mechanisms were observed from the experiment and three different deformation processes were also identified. The effects of aluminum foam, pleated plate thickness and angle θo (the angle between flat plate and pleated plate) as well as pleat number on the energy absorption performance of the connector were experimentally investigated, which showed that the energy absorption capacity could be improved by filling the connector with aluminum foam and increasing the pleated plate thickness, angle θo and pleat number. Moreover, an analytical model for determining the load–displacement curve of the energy absorption connector was also developed and the predictions by the analytical model were proven to be reasonable by comparing with the experimental data.